The Effect Of Pore Size Distribution On Gold Adsorption By Magnetic Activated Carbons - Gustavo A. Munoz (The Minerals, Metals and Materials Society, 2003)
Activated carbons owe their adsorption capacities to their extensively developed pore network structure. As a result, these adsorbents generally exhibit high specific surface areas. Currently, granular activated carbons produced from coconut shells are traditionally used for gold recovery by adsorption from cyanide leaching solutions. Magnetic activated carbons (MACs) for gold recovery from cyanide solutions produced from sources other than coconut shells have been developed at the University of Utah by mixing a magnetic precursor with a carbon source, and treating the mixture under controlled conditions of temperature and gas phase composition. The pore size distribution of the activated carbons is dependent on the degree of activation, among other factors. The significance of the MAC pore size distribution on gold adsorption kinetics and gold adsorption capacity is presented.